Uncovering placemaking needs with(in) a kindergarten community: a cross-disciplinary approach to participatory design - Economidou, Eléni; Gerner, Nathalie; Pichler, Christina; Hartl, Arnulf; Frauenberger, Christopher (Frontiers in Psychology, 2023)
Introduction The design of early childhood education and care facilities faces the double challenge of creating a stimulating environment for young children and a supportive workplace for staff. The existing body of research suggests that placemaking strategies serve both requirements. A promising approach to meet placemaking needs is the participation of future occupants in the building design. Methods We pursued a participatory design study with the community of an Austrian kindergarten aiming to inform the future building renovation. We combined novel cultural fiction probes methods with conventional inquiry methods to gather information from children and teachers about their experience of the built environment. Using thematic and content analyzes we explored placemaking needs from different epistemic perspectives and converged findings through iterative exchange. Results Returns of children and teachers were interconnected and complementary. From a design-oriented perspective, children’s experience of place was relatable to spatial, temporo-spatial, and acoustic qualities as well as control needs. From a human-centered perspective, teachers’ experience of place was relatable to the needs of feeling embedded, protected, enacted, and socially connected. The converged findings revealed dynamic placemaking processes involving the elements of space, time, and control at different levels. Discussion Cross-disciplinary collaboration and research consolidation brought forth valuable insights on supportive structures for both children and teachers, facilitated timely knowledge transfer, and converted into design solutions that foster enacted placemaking. Albeit general transferability is limited, findings are interpretable within a solid framework of existing theories, concepts and evidence.